2018
DOI: 10.1039/c7tc04986b
|View full text |Cite
|
Sign up to set email alerts
|

Polypyridyl chromium(iii) complexes for non-volatile memory application: impact of the coordination sphere on memory device performance

Abstract: To gain insights into the molecular design, the memory devices of various Cr(iii) complexes have been studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…4,5 Accordingly, the solubility, stability, redox potential and kinetics, and optical characteristics of metal− polypyridyl complexes can be controlled and manipulated in a desired way. For these reasons, functional polypyridyl complexes have found great utility in the design of metallosupramolecular architectures 6 as well as active elements in photodynamic therapy, 7,8 catalysts, 9,10 sensing modules, 11,12 components of nonvolatile memory devices, 13,14 photochromic or electrochromic elements in solid-state devices, 15,16 and media for charge and spin transport. 17,18 Most of these applications rely on covalent or noncovalent assembly of polypyridyl complexes on suitably functionalized solid substrates, which provide aligned and densely packed nanometric architectures, with a much better control over molecular orientation, integrity, and functionality compared to the liquid media case.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Accordingly, the solubility, stability, redox potential and kinetics, and optical characteristics of metal− polypyridyl complexes can be controlled and manipulated in a desired way. For these reasons, functional polypyridyl complexes have found great utility in the design of metallosupramolecular architectures 6 as well as active elements in photodynamic therapy, 7,8 catalysts, 9,10 sensing modules, 11,12 components of nonvolatile memory devices, 13,14 photochromic or electrochromic elements in solid-state devices, 15,16 and media for charge and spin transport. 17,18 Most of these applications rely on covalent or noncovalent assembly of polypyridyl complexes on suitably functionalized solid substrates, which provide aligned and densely packed nanometric architectures, with a much better control over molecular orientation, integrity, and functionality compared to the liquid media case.…”
Section: Introductionmentioning
confidence: 99%
“…121 In 2018, Roy et al reported a series of homoleptic and heteroleptic polypyridyl Cr(III) complexes by varying the bidentate diamine ligands, [Cr(N-N) 2 (N-N 0 )]X 3 , where N-N = 1,10-phenanthroline, N-N 0 = 4,4 0 -dimethyl-2,2 0bipyridine, 3,4,7,8-tetramethyl-1,10-phenanthroline, 5,6-dibromo-1,10-phenanthroline or 4,4--bis(methoxycarbonyl)-2,2--bipyridine, X = CF 3 SO 3 À or PF 6 À counter anion (S30-S34). 122 The memory devices based on these solution-processable Cr(III) complexes (Al/S30-S34/Al) were fabricated by the facile spin-coating technology, and the structure-memory performance relationship was then systematically investigated. The I-V curves of the devices based on S30 and S31 show a reversible and stable bipolar flashtype switching characteristic with the high I ON /I OFF ratios of 10 4 and 10 6 , respectively (see Fig.…”
Section: Rram Devices Based On Small-molecule Organometallic Complexesmentioning
confidence: 99%
“…Organometallic complexes (OMCs) have also attracted great interest for resistive memory switching in recent years. Many research teams have successfully synthesized OMCs for information storage applications 35,40,170‐179 . OMCs are usually made of transition metals with well‐defined coordination structures and surrounding ligands.…”
Section: Organic‐inorganic Hybrid Materials For Resistive Memorymentioning
confidence: 99%